Los claroscuros del debate. Pueblos Indígenas, Colonialismo y Subalternidad en América del Sur. Siglos XX y XXI - Canales, Pedro; Moreno, Mariana (Ariadna Ediciones, 2016)
History and culture of Latin American ethnic communities and political challenges today